2013
DOI: 10.3389/fmicb.2013.00187
|View full text |Cite
|
Sign up to set email alerts
|

Macaque-tropic human immunodeficiency virus type 1: breaking out of the host restriction factors

Abstract: Macaque monkeys serve as important animal models for understanding the pathogenesis of lentiviral infections. Since human immunodeficiency virus type 1 (HIV-1) hardly replicates in macaque cells, simian immunodeficiency virus (SIV) or chimeric viruses between HIV-1 and SIV (SHIV) have been used as challenge viruses in this research field. These viruses, however, are genetically distant from HIV-1. Therefore, in order to evaluate the efficacy of anti-HIV-1 drugs and vaccines in macaques, the development of a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 198 publications
(220 reference statements)
1
12
0
Order By: Relevance
“…Therefore, NHP represent an important tool and animal model for the HIV/AIDS cure research community. NHP models including monkeys, African green monkeys, macaques provides a suitable means of investigating the pathogenesis, immunology and immunohistochemistry of the HIV disease; and this is usually due in part to the genetic, physiological and anatomical relatedness of the NHPs and their human counterparts [81][82][83]. Several studies have shown that the infection of NHPs with the virulent strain of simian-human immunodeficiency viruses (SHIV) results in a similar disease that closely resembles HIV-1 infection in humans [82,84].…”
Section: Non-human Primate Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, NHP represent an important tool and animal model for the HIV/AIDS cure research community. NHP models including monkeys, African green monkeys, macaques provides a suitable means of investigating the pathogenesis, immunology and immunohistochemistry of the HIV disease; and this is usually due in part to the genetic, physiological and anatomical relatedness of the NHPs and their human counterparts [81][82][83]. Several studies have shown that the infection of NHPs with the virulent strain of simian-human immunodeficiency viruses (SHIV) results in a similar disease that closely resembles HIV-1 infection in humans [82,84].…”
Section: Non-human Primate Modelmentioning
confidence: 99%
“…Thus, HIV-1 pathogenesis cannot be studied directly using these monkeys. Instead, SIV, the NHP relative of HIV-1 is currently being used to study HIV-1 pathogenesis in RMs due to the similarities of these two viruses (i.e., SIV and HIV); and many laboratories and ours now have HIV-1 models (for example, HIV-1 macaque tropic, HIV-1mt strains) that can infect monkeys (RMs for example) and initiate similar clinical episodes associated with HIV-1 pathogenesis in humans [81]. These animal models are important tools for achieve this, but first of all, Africa is in dire need of high-tech research laboratories and research scientists who will collaborate and do world-class research with their counterparts across the world in order to find a lasting cure to this pandemic.…”
Section: Non-human Primate Modelmentioning
confidence: 99%
“…An intensified focus on the genetics of interspecies transmission may help researchers determine if there are fundamental rules that can be used to help predict the likelihood of specific zoonoses and new emerging viral diseases. Understanding the genetics of restriction and intrinsic immunity also has practical benefits for animal models of AIDS, most of which are currently based on genetically outbred primates – for example, as some of the blocks to HIV-1 infection have been identified, several groups have been able to engineer simiantropic HIV-1 strains that circumvent restriction and replicate in macaques [126128]. Moreover, because genetic variation in restriction factor genes is likely to be a confounding element in small, preclinical vaccine and pathogenesis studies in macaques, identifying and accounting for the contributions of different loci can be used to improve the statistical evaluation of outcomes.…”
Section: Future Perspectivementioning
confidence: 99%
“…Also, a bovine model for HTLV-1 pathogenesis has been described by Aida et al ( 2013 ). Challenging new attempts to establish human immunodeficiency virus type 1 (HIV-1)/macaque infection models have been reviewed by Misra et al ( 2013 ), and also by Saito and Akari ( 2013 ). Another approach to understand HIV-1 biology in vivo has been described by Matsuyama-Murata et al ( 2013 ).…”
mentioning
confidence: 99%